Unmasking of miliary tuberculosis in COVID-19: A case report (Indian Journal of Case Reports, 2021)
Both coronavirus disease-19 (COVID-19) and pulmonary tuberculosis (PTB) are transmitted through the respiratory route and are related to various risk factors. The index case was a 45-year-old female who presented to a tertiary care hospital in North India with complaints of dry cough, loss of weight, and appetite for twenty days followed by fever and dyspnea for five days. RT-PCR for COVID-19 turned out positive. Chest-roentgenogram revealed bilateral homogenous micronodules. She was started on COVID-19 treatment according to the Ministry of Health and Family Welfare guidelines. She was not clinically improved so CECT-thorax was performed which revealed bilateral homogenous millet-shaped micronodular opacities. Mantoux test was twenty-five millimeters in size but sputum analysis for acid-fast bacilli was negative. The patient was started on anti-tubercular-therapy (ATT). The patient got improved clinically and is being followed. This case focuses on the need for prompt diagnosis of PTB in COVID patients for the appropriate management and early recovery.